The Effect of Project Methods on Environmental Care Behavior in Early Childhood during a Pandemic - Yuli Surohmah; Lilis Madyawati; Febru Puji Astuti (Prosiding University Research Colloquium, 2022)
This study aims to determine the effect of the project method on environmental care behavior in early childhood during the Covid 19 pandemic. The research sample was in Kindergarten B group children at PAUD Pandan Wangi Secang, Magelang Regency. This research was conducted because there were problems of environmental care behavior during the pandemic related to environmental cleanliness. The low level of environmental care behavior during this pandemic will be increased through the project method. The design of this study used an Experimental Research model of Pre-experimental design in the form of One Group Pretest-Posttest Design, namely through pretest, treatment, and posttest. The research was conducted in three stages including preparation, implementation, and evaluation. The subjects in this study were children in the TK B group, totaling 30 children. Data collection techniques using observation and interviews. Analysis of the data used is a parametric test. The results showed an increase in children's environmental care behavior during the pandemic through the project method. This is evidenced by the comparison of the pretest results showing the lowest score of 15, the highest value of 23, and the average value of 19. Meanwhile, the posttest results showed the lowest score of 34, the highest score of 43, and the average value of 38.9. Based on these scores, it can be concluded that the project method has an effect on children's environmental care behavior during the pandemic in Kindergarten B Group at PAUD Pandan Wangi Secang Magelang.